La práctica y el comportamiento axiológico de los padres de familia y docentes, y su incidencia en el aprendizaje de los estudiantes de noveno y décimo grado del subnivel básica superior de educación general básica en la unidad educativa “Julio Ernesto Celi” de la parroquia Jimbura, cantón Espíndola, periodo 2013 - Paladinez Sanchez, Carmen Lucia (2014)
This research entitled "Practice and axiological behavior of Parents and Teachers, and their impact on student learning Ninth and Tenth Grade Basic sublevel Superior General Education in Basic Education Unit "Julio Ernesto Celi", was aimed at rescue and practice of values in educational institutions of the country, region, province and county. Currently globalization has brought to the developing crisis in all aspects, not just economic, social, political, cultural and environmental; but specifically in the axiological either in the family, school and society. He had a general practice to diagnose and behavior of parents and teachers and its impact on student learning in ninth and tenth grade Basic Sublevel Superior General Education Basic Education Unit "Julio Ernesto Celi" the Jimbura parish, canton Espindola. After completion of the field research he came to the conclusion that the establishment does not include teachers in the curriculum of the respective years, treatment of values in the integral formation of the student. It is recommended that the committees of the institution organize workshops to the rescue of institutional values in order to promote the Good Life in the community.